Modern Perspectives of Logistics Transport in Economics: Empirical Studies in Ho Chi Minh, Vietnam Vol. 1 - Vu Thi Kim Hanh (Modern Perspectives of Logistics Transport in Economics: Empirical Studies in Ho Chi Minh, Vietnam Vol. 1, 2021)
The paper focuses on assessing of transportation logistics (TL) consists of three its sub-sectors are Road transportation (RT), Inland Water Transportation (IWT) and Sea Transportation (ST). Logistics transportation systems have developed and experienced in many ways over time. The evolution along with a history of transportation system. Because of the case for any system, because it grows so makes its impact on societies and day to day life. The increased growth of usage of the transportation systems across all modes can change to be better suited for each society and that time period in which it is needed. The author propose the MLR, ARCH MLR and GARCH (a,b) MLR which a =1, and b =1 to assess the dependence of GDP of TL on GDP of its three sub-sectors which are RT, IWT, and ST, and GDP of TL is dependent variable, there are three independent variables are GDP of RT, GDP of IWT, and GDP of ST. Based on the analytical results and findings giving conclusion is model MLLH-AFLR and model LMLR are high statistical significance and reliable, hence it is able to apply for not only Air Transportation Logistics but also it can be applied to other scopes which has similar characteristics and similar operations method to Air Transportation Logistics. Using LMLR model to assess other factors of Air Transportation Logistics, and author will develop to other kind of transportation like Road, Rail, Inland water, Sea ways.